Respostas neuromusculares e fisiológicas ao treinamento resistido de alta intensidade (HIRT) - AZEVEDO, Antenor Barbosa Calandrini de (2019)
The objective of the present study was to investigate the effect of High Intensity Resistance Training (HIRT) in comparison to Traditional Resistance Training (TRT) on biochemical variables and vertical jump performance of university students. Twelve physically active undergraduates performed the HIRT or TRT in two separate sessions at 5 days intervals. Subsequently, vertical jumping procedures were performed through Countermovement Jump (CMJ), blood tests in the PRE, POST, 24h and 48h periods. For the comparisons of means between moments, Variance Analyses (ANOVA) was applied for repeated measurements and, where appropriate, the differences were tested through Bonferroni post-hoc. In addition to the Effect Size (ES), established according to Cohen´s d. The results showed a significant diffrence between protocols for CMJ only at the moment (PRE-POST; p=0,05). As, for Creatine Kinase difference between protocols in the moment, (PRE-PÓST; p=0,05). However, no significant differences were found at the moments (POST-24h; p=0,53) e (24h-48h; p=0,20). Additionally, no differences were found between protocols for Creatine Kinase MB (PRE-POST; p=0,63), (POST-24h; p=0,14). However, for the moment 24h-48h a difference was found (p=0,002). Additionally, Aspartate Aminotransferase (PRE-POST; p=0,30), (POST-24h; p=0,53) and (24h-48h; p=0,90), e Alanine Aminotransferase (PRE-POST; p=0,55), (POST-24h; p=0,28) and (24h-48h; p=0,11), no differences were found between protocols. We conclude that HIRT demonstrated similar responses to TRT in biochemical variables. However, the performance of vertical jumps demonstrated a supeior reduction of the HIRT in relation to the TRT, nevertheless, the basal values returned in 24h for both methods.